Contemporary Issues in Accounting The Current Developments in Accounting Beyond the Numbers (Springer International Publishing, 2018)
The book explores the developing challenges and opportunities within the business and finance world which are likely to impact the accounting profession in the near future. It outlines a number of approaches to ensure that the accountants of the future are equipped with a useful awareness of some of the key topic areas that are quickly becoming a reality and helps bridge the gap between academia and practice. The chapters are standalone introductory pieces to provide useful précis of key topics and how they apply to the accounting profession in particular. It aims to deliver key readings on 'hot topics' not addressed in other texts which the accounting profession is tackling or are likely to tackle soon. Hence the book provides accounting students and researchers a solid grounding in a broad range of highly relevant non-technical accounting themes, looking at the bigger environment in which future accountants will be operating, involving considerations of strategic corporate governance issues and highlighting competences beyond the standard technical accounting skill sets.